Correlation between interdialytic weight gain, left ventricular hypertrophy and FGF- 23 in prevalent hemodialysis patients - Shawky, Sahar Mahmoud; Khalifa, Maha Mohamed Mohamed; Amin, Kholoud Mahmoud; Hassan, Mohamed Saeed (Journal of Clinical Nephrology, 2020)
Background:Patients with end-stage renal disease are suspected to have significant volume shifts and thereby cardiovascular strain as a result to interdialytic weight gain, chronic fluid overload and fluid removal during dialysis. In long-term hemodialysis patients, higher IDWG (interdialytic weight gain) could be associated with poor survival. Patients with the lowest interdialytic weight gain have the greatest survival. Certain laboratory and imaging modalities could help to assess and monitor the appropriate fluid balance for hemodialysis patients. FGF -23 might be associated with cardiovascular morbidity in ESRD patients. Objective: To evaluate correlation between hypervolemia and left ventricular hypertrophy and FGF-23 in hemodialysis patients. Patients and Methods: This cross sectional study was conducted on 60 prevalent hemodialysis patients. Patients were divided into two groups according to interdialytic weight gain (IDWG): Group I (low IDWG): Patients with absolute weight gain < 3 kg. Group II (high IDWG): patients with weight gain ≥ 3 kg. FGF 23, routine laboratory tests and echocardiography were done for both groups. Results: high IDWG group has higher systolic blood pressure and LVMI than low IDWG group. In all patients group, FGF-23 had a positive correlation with (weight gain, Na, PO4, PTH, systolic, diastolic blood pressure, LV wall septal and posterior wall thickness and left ventricular mass index) and had a negative correlation with Hb level. Conclusion: FGF-23 could be a marker of volume overload and LVH in ESRD patients, which affect morbidity and mortality in these patients. FGF- 23 might be a marker of anemia in ESRD as it has a negative correlation with HB.